Drug-drug interactions in polypharmacy patients: The impact of renal impairment - Bianca Papotti; Cinzia Marchi; Maria Pia Adorni; Francesco Potì (Elsevier, 2021)
Chronic kidney disease (CKD) is a long-term condition characterized by a gradual loss of kidney functions, usually accompanied by other comorbidities including cardiovascular diseases (hypertension, heart failure and stroke) and diabetes mellitus. Therefore, multiple pharmacological prescriptions are very common in these patients. Epidemiological and clinical observations have shown that polypharmacy may increase the probability of adverse drug reactions (ADRs), possibly through a higher risk of drug-drug interactions (DDIs). Renal impairment may further worsen this scenario by affecting the physiological and biochemical pathways underlying pharmacokinetics and ultimately modifying the pharmacodynamic responses. It has been estimated that the prevalence of DDIs in CKD patients ranged between 56.9% and 89.1%, accounting for a significant increase in healthcare costs, length and frequency of hospitalization, with a detrimental impact on health and quality of life of these patients. Despite these recognized high-risk conditions, scientific literature released on this topic is still limited. Basing on the most commonly prescribed therapies in patients with CKD, the present short review summarizes the current state of knowledge of the putative DDIs occurring in CKD patients undergoing polytherapy. The most relevant underlying mechanisms and their clinical significance are also debated.